Neuroscience Meets EdTech : Combating Mathematics Anxiety - Nur Fazliana, Rahim; Farah Liyana, Azizan; Noor Azreen, Mohd Khushairi; Wan’ Aliaa, Wan Anis (RSIS International, 2025)
Mathematics anxiety continues to be a pervasive issue in education, contributing to decreased self-confidence, reduced motivation, and lower academic performance among students. This paper explores an integrated pedagogical framework that combines the Brain-Based Teaching Approach (BBTA) with technology-enhanced learning as a strategic intervention to mitigate these challenges. Drawing on neuroscience principles, BBTA emphasizes creating a supportive emotional climate, sustaining learner engagement through meaningful tasks, and promoting active processing of knowledge. Evidence from previous studies demonstrates that BBTA, when supported by technology, leads to a measurable reduction in mathematics anxiety, significant improvement in motivation, and enhanced achievement across varying levels of task difficulty. This paper outlines the theoretical basis for the integrated model, discusses its application in the mathematics classroom, and explores its scalability to other disciplines. This paper concludes with recommendations for the potential of BBTA with technology integration as a sustainable, research-informed strategy for fostering both cognitive development and emotional well-being in mathematics education